Peculiarities of surgical treatment of gastrointestinal tract combined congenital malformations in newborns - Makarova, М. О.; Макарова, Марина Олександрівна (Zaporizhzhia state medical university, 2017)
Congenital gastrointestinal (GI) malformations make up 21–25 % of all congenital anomalies and require surgical correction in the neonatal period. The aim was to analyze the methods of operative treatment of hard composite congenital gastrointestinal malformations in infants. Materials and Methods. There were 13 newborns with gastroschisis, omphalocele and esophageal atresia combined with intestinal atresia, anal atresia and also with congenital heart defects in our study. Results. We have designed new preoperative care strategies for the newborns. All combined GI defects were corrected in one step. In gastroschisis and omphalocele in combination with small intestine atresia we made a plastic of anterior abdominal wall, bowel segment resection and anastomosis end-to-end. In esophageal atresia and atresia of the anus direct esophago-esophagoanastomosis was applied with suturing of tracheoesophageal fistula, also in two patients proctoplasty by Pena 2 was carried out, and in one patient with high anal atresia colostomy was applied, which was closed in the age of 6 months. In case of esophageal atresia combined with small intestine atresia direct esophago-esophagoanastomosis with tracheoesophageal fistula suturing was carried out, and resection of the bowel segment with anastomosis end-to-end was applied. In a patient with a combination of esophageal atresia and duodenal obstruction esophagoplasty and closure of tracheoesophageal fistula with anastomosis by Kimur was made. Preference was given to the combined anesthesia with neuraxial blockade. Postoperative care included prolonged artificial lung ventilation, anesthesia, parenteral nutrition, antibacterial and antifungal medicines. Conclusions. One-step correction of the congenital GI malformations in newborns is effective and it gives opportunity to achieve the best results with a single surgical intervention. Extremely important links of the combined GI defects therapy is timely and balanced preoperative preparation, anesthetic management with the advantage of neuraxial blockade usage, as well as careful postoperative management of the patient. Вроджені вади розвитку шлунково-кишкового тракту (ШКТ) становлять 21–25 % усіх уроджених аномалій і потребують хірургічної корекції у періоді новонародженості. Мета роботи – аналіз методів оперативного лікування тяжких комбінованих уроджених вад розвитку ШКТ у новонароджених. Матеріали та методи. Під спостереженням перебували 13 новонароджених дітей із гастрошизисом, омфалоцеле та атрезією стравоходу в комбінації з атрезією тонкого кишечника або ануса, а також із вродженими вадами серця. Результати. Розробили схеми передопераційної підготовки для новонароджених. Усі комбіновані вади ЖКТ скоректовані за один етап. При гастрошизисі та омфалоцеле в поєднанні з атрезією тонкої кишки проводилась пластика передньої черевної стінки, резекція ділянки кишки та накладення анастомозу кінець у кінець. При атрезії стравоходу та атрезії ануса накладався прямий езофаго-езофагоанастомоз з ушиванням трахеостравохідної нориці, а також у двох пацієнтів здійснювалась проктопластика за Пена 2, а в одного пацієнта з високою атрезією ануса була накладена колостома, що надалі була закрита у 6-місячному віці. У пацієнта з поєднанням атрезії стравоходу та дуоденальної непрохідності здійснили езофагопластику, ушивання трахеостравохідної нориці, а також накладення анастомозу Кімура. Під час анестезіологічного забезпечення перевага надавалася комбінованій анестезії з використанням центральних нейроаксіальних блокад. Післяопераційне ведення містило пролонговану штучну вентиляцію легенів, знеболювання, парентеральне харчування, антибактеріальні та антимікотичні препарати. Висновки. Одноетапна корекція комбінованих уроджених мальформацій ШКТ у новонароджених ефективна та дає можливість досягти найкращих результатів під час єдиного хірургічного втручання. Винятково важливими ланками терапії комбінованих вад ШКТ є своєчасна та збалансована передопераційна підготовка, анестезіологічне забезпечення з переважним використанням нейроаксіальних блокад, а також ретельне післяопераційне ведення пацієнта.
Особливості хірургічного лікування комбінованих вроджених вад розвитку шлунково-кишкового тракту в новонароджених
Keywords: newborn; gastroschisis; esophageal atresia; intestinal atresia; surgical procedures operative; новонароджений; гастрошизис; атрезія стравоходу; атрезія кишечника; оперативне лікування